Sustainability, livability and wellbeing in a bionic internet-of-things - John Canning; Yunlong Guo; Zenon Chaczko (Optical Materials: X, 2022)
To address climate change, environmental monitoring and wellness more generally on a global scale, a new concept is presented - the bionic internet-of-things, or b-IoT. We propose the utilization of existing organic “sensor” technology that nature has provided and discuss a future adapting these to an existing inorganic internet to truly open up a global IoT. The use of organisms, in the first instance plants, bring an additional physical and psychological factor, connecting up living in things in a way that is consistent with natural symbiosis but extended over a global and potentially galactic scale. These plants not only monitor the environment, they interact to enable it to thrive, producing an ecosystem that consumes CO2, generates oxygen, recycling land and providing an environment for other organic species to develop. In contemporary real estate development, the need for a more whole ecosystem approach is recognized and that technology plays a vital role towards that. Thus, we identify wellness and wellbeing as an integral part of all future technology development. A fundamental challenge is connecting such sensors to the IoT. We briefly review technologies of relevance in the context of material, health and environmental considerations, and discuss novel transducer mechanisms. To assess sensor capability, we review our recent work on measuring leaf material properties using contact angle mapping, demonstrating a diversity of potential for environmental monitoring from this method alone. We also review some examples of common botanical properties that already exist which can in principle be readily coupled to existing transducers to create the hybrid b-IoT. We briefly speculate into the future of materials at the sensor end and into reaching space that can meet low cost and provide advanced functionality to help connectivity and integrate fibre and fibreless technologies.